Impacts of environmental conditions, and allelic variation of cytosolic glutamine synthetase on maize hybrid kernel production - Nardjis Amiour (Nature Portfolio, 2021)
Amiour et al. use a multi-year field trial evaluation and association mapping to determine if increased enzyme activity and native allelic variations at the GS1 loci in maize contribute to differences in grain yield. Overexpression of GS1 and polymorphisms in the corresponding loci were associated with kernel yield, indicating that GS1 expression can directly control kernel production and that GS1 has a potential lead in the production of high yielding maize hybrids depending on environmental conditions.